The performance of the modified pump motor as a generator on the Pump as Turbine (PAT) power plant. (May 2019) - Zariatin, D L; Fitria, S N; Dewanto, Y; Ismail; Rahmalina, D
Abstract: There are many types of the hydropower plant. Pump as Turbine (PAT) is one of the simple, practical and low-cost hydropower plants. In PAT technology, a commercial pump available in the market can be modified to become a PAT power plant. This paper is a technical note that describes the guideline to modify the induction pump motor into a generator and analyze the performance of the generator. There are two aspects that must be considered in modifying the motor, namely the motor construction and the output power. In modifying the motor pump, the magnet must be inserted in the rotor. Meanwhile, the wire diameter and the number of winding in the stator are modified to increase the voltage working range. The experimental tests were performed with a laboratory scale PAT power plant to identify the generator performance. The analysis showed that a modified pump motor generated 32.5 VAC and 0.33 Ampere of electrical power (10.725 Watt), only with 2.5 m of water head. The electrical power generated could be improved with a higher water head.